KARAKTER VISUAL FASADE BANGUNAN BERDASARKAN TEORI HAMID SHIRVANI DAN D.K. CHING (Studi Kasus: Hotel di Kawasan Business on Boulevard Manado) - Lintong, Steven; Mandey, Johansen Cruyff; Kalalo, Loudy Moody Barce (Universitas Negeri Gorontalo, 2025)
Hamid Shirvani emphasizes the importance of combining contemporary elements with local cultural and historical heritage in architectural design. This is reflected in his work, which often combines modern ideas with traditional elements, creating a harmony between the past and the present in building design. In addition, Shirvani also highlights the importance of social, cultural and economic context in sustainable urban design. Francis D.K. Ching in a famous theory states that it is important to understand the basic principles of formation, space and sequence in architectural design. Through his in-depth approach to the basic elements of architecture, Ching championed concepts such as scale, proportion, negative and positive space, and spatial organization in architectural design. He also highlighted the importance of the use of form, texture and lighting in creating meaningful and functional buildings. This research aims to analyze the visual character of building facades that function as 3 and 4 Star Hotels in the Business on Boulevard area of Manado City, which is located between the junction of Taman/Patung Piere Tendean and Sario Bridge/River. The hotels are Lion hotel, Quality hotel, Big Fish hotel, Four Points hotel and Ibis hotel. This research will focus on the components and architectural composition of the facade design that reflects the desired identity, image and visual character to meet operational needs as a hotel and at the same time attract market interest in the context of business in the area. The research method used is qualitative by involving direct observation of Hotel buildings that are already operating in the research location, as well as interviews with industry players and related stakeholders. From the research results, it was found that Hamid Shirvani's Theory and the rules of D.K. Ching were clearly visualized in the 5 research objects. Most of the components and compositions have been applied to the building facade elements. In general, it can be concluded that the visual character of the building facade in the 5 hotels that became the research sample is very strong and dominantly applies the theory of Hamid Shirvani and D.K. Ching both from the component elements and the composition elements. Keywords: building, facade, visual character